Penerapan Model Pembelajaran Student Teams Achievement Division Untuk Meningkatkan Kemampuan Penalaran Matematis Siswa di Kelas VIII MTsN 2 Medan - Lubis, Putri Wildayani; Hasratuddin, Hasratuddin (CV. Ulil Albab Corp, 2024)
The aim of this research is to improve students' mathematical reasoning abilities after implementing the Student Teams Achievement Division (STAD) learning model. The subjects of this research were 32 students in class VIII-8 MTsN 2 Medan. The object of this research is the application of the Student Teams Achievement Division learning model. The type of this research is classroom action research. Data was collected through two reasoning tests in the form of essays. The Reasoning Ability Test I was carried out after Action I (Cycle I) which consisted of 4 questions, and the Logic Ability Test II was carried out after Action II (Cycle II) which consisted of 4 questions. The results of the research show an increase in students' mathematical thinking abilities which can also be seen in the results of their mathematical reasoning tests. Before action was taken, the average diagnostic test score was 39.75 and the overall level of thinking was in the very low thinking category for 2 students (6.25%). After carrying out Cycle I actions using STAD type cooperative learning, the average Reasoning Ability Test score increased to 69.68 and as many as 22 people (68.75%) had a poor level of reasoning ability, meaning that the class average increased by 29. 73. After the Cycle II actions were carried out, the average score for the Mathematical Reasoning Test II was 84.28 with a total of 29 students (90.63%) who were in the high completion category, meaning that the average score achieved had increased by 21. 15. Thus it can be concluded that learning using the STAD type cooperative learning model can improve students' mathematical reasoning abilities in class VIII-8 MTsN 2 Medan.